Preparation method and application of tetrapod-shaped carbon nitride nanorods

CN118754068BActive Publication Date: 2026-10-09GUIZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410845423.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-27
Publication Date
2026-10-09
Estimated Expiration
2044-06-27

AI Technical Summary

Technical Problem

但是普通的热缩聚法合成的氮化碳为块状形貌,尺寸较大,比表面积小,导致光生载流子分离效率降低,催化活性较差

Benefits of technology

[0020] The beneficial effects of this invention are as follows: the prepared tetragonal prism-shaped carbon nitride nanorods have sufficiently small nanoscale size and a special tetragonal prism morphology, making them less prone to aggregation. They also possess ample nanopores, resulting in at least three significant improvements compared to bulk carbon nitride: firstly, the specific surface area is increased, leading to more active reaction sites; secondly, the porous structure shortens the distance photogenerated carriers migrate to the catalyst, thereby improving the photogenerated carrier separation efficiency; and thirdly, the structured carbon nitride has a narrower band gap, broadening its light absorption range and enhancing its light absorption and response capabilities. This invention exhibits good degradation effects on various organic pollutants, good recyclability, and high practicality, making it significant for the efficient removal of organic pollutants from water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754068B_ABST
    Figure CN118754068B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of nanometer material science, and provides a preparation method of tetrapod-shaped carbon nitride nanorods, which uses tetrapod-shaped nanometer silica tubes as a hard template, soaks the tetrapod-shaped nanometer silica tubes in a polar solvent, adds carbon nitride precursors, evaporates the solvent overflowed during drying, and obtains the tetrapod-shaped carbon nitride nanorods through calcination and etching processes. The present application also provides an application of the tetrapod-shaped carbon nitride nanorods. The tetrapod-shaped carbon nitride nanorods prepared by the present application have a small nanometer size and a special tetrapod-shaped morphology, are not prone to agglomeration, have sufficient nanometer channels, and have multiple aspects of obvious improvement compared with block-shaped carbon nitride, have a good degradation effect on various organic pollutants, have good recyclability, have high practicality, and have important significance for efficient removal of organic pollutants in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing tetragonal prism-shaped carbon nitride nanorods, belonging to the field of nanomaterials science and technology. Background Technology

[0002] Carbon nitride, as a metal-free semiconductor material responsive to visible light, has attracted widespread attention from researchers due to its excellent characteristics such as ease of synthesis, low cost, non-toxicity, and high physicochemical stability, making it highly promising for applications in photocatalysis. However, carbon nitride synthesized by the conventional thermal polycondensation method has a bulk morphology, large size, and small specific surface area, resulting in reduced photogenerated carrier separation efficiency and poor catalytic activity.

[0003] To further improve the catalytic activity of carbon nitride, researchers have made numerous attempts. Vinu et al. first used silica SBA-15 as a hard template to increase the porosity of carbon nitride, obtaining a larger surface area and an ordered pore structure. However, due to low thermal stability and a very low carbon-to-nitrogen ratio, the stability was very low, and the resulting morphology was also relatively simple. Furthermore, current improvements to the morphology of carbon nitride photocatalysts include spherical, sheet-like, and rod-like shapes. Among these, rod-shaped carbon nitride has advantages such as greater dispersion and a larger specific surface area, but it is mostly a macroporous structure, lacking the important advantages of micropores and mesopores in charge carrier transfer and transport. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for preparing tetragonal prism-shaped carbon nitride nanorods. This method can enhance the catalytic performance and expand the applications of carbon nitride by controlling its special structure and morphology, thereby significantly improving the photocatalytic activity of carbon nitride.

[0005] The present invention is achieved through the following technical solutions.

[0006] The present invention provides a method for preparing tetragonal prism-shaped carbon nitride nanorods, which uses tetragonal prism-shaped silica nanotubes as hard templates, impregnates the tetragonal prism-shaped silica nanotubes with a polar solvent, adds carbon nitride precursors, evaporates the solvent after drying, and obtains tetragonal prism-shaped carbon nitride nanorods through calcination and etching processes.

[0007] The specific steps are as follows:

[0008] S1. Prepare a gel-like liquid by mixing square prism-shaped nano-silica tubes with a polar solvent;

[0009] S2. Add carbon nitride precursor to the gel-like liquid, heat and stir at 100°C until homogeneous to obtain a white solid.

[0010] S3. Heat the white solid to 500-550℃ at a heating rate of 2-5℃ / min, then calcine it in a muffle furnace for 2-4 hours, and cool it to room temperature to obtain a pale yellow solid.

[0011] S4. Place the pale yellow solid in a 5M-10M HF solution and stir to etch for 24-48 hours. Then filter and wash until neutral. After drying overnight, the yellow solid, namely the tetragonal prism-shaped carbon nitride nanorods, is obtained.

[0012] The polar solvent is N,N-dimethylformamide.

[0013] The mass ratio of the carbon nitride precursor to the tetragonal prism-shaped nano-silica tubes is 1 to 3:1.

[0014] The carbon nitride precursor is any one of thiourea, dicyandiamide, melamine, 3-amino-1,2,4-triazole, and 5-amino-1H-tetrazole.

[0015] The diameter of the quadrangular prism-shaped nano-silica tube is 52nm to 123nm.

[0016] The mass ratio of the carbon nitride precursor to the tetragonal prism-shaped nano-silica tubes is 2:1.

[0017] The carbon nitride precursor is 3-amino-1,2,4-triazole.

[0018] The drying conditions in step S4, which involve drying overnight, are 60°C.

[0019] This invention also provides an application of tetragonal prism-shaped carbon nitride nanorods, wherein the tetragonal prism-shaped carbon nitride nanorods prepared by the method described above are applied to the photocatalytic degradation of antibiotics in wastewater.

[0020] The beneficial effects of this invention are as follows: the prepared tetragonal prism-shaped carbon nitride nanorods have sufficiently small nanoscale size and a special tetragonal prism morphology, making them less prone to aggregation. They also possess ample nanopores, resulting in at least three significant improvements compared to bulk carbon nitride: firstly, the specific surface area is increased, leading to more active reaction sites; secondly, the porous structure shortens the distance photogenerated carriers migrate to the catalyst, thereby improving the photogenerated carrier separation efficiency; and thirdly, the structured carbon nitride has a narrower band gap, broadening its light absorption range and enhancing its light absorption and response capabilities. This invention exhibits good degradation effects on various organic pollutants, good recyclability, and high practicality, making it significant for the efficient removal of organic pollutants from water. Attached Figure Description

[0021] Figure 1 This is a flowchart illustrating at least one embodiment of the present invention;

[0022] Figure 2 These are comparative SEM images of the tetragonal prism-shaped carbon nitride nanorods and the original carbon nitride in this invention.

[0023] Figure 3 This is a graph showing the performance of photocatalytic degradation of tetracycline hydrochloride by prismatic carbon nitride nanorods and raw carbon nitride in an experimental example.

[0024] Figure 4 This is a comparison of nitrogen adsorption-desorption curves between prismatic carbon nitride nanorods and pristine carbon nitride in an experimental example.

[0025] Figure 5 This is a performance curve of a cyclic experiment of a tetragonal prism-shaped carbon nitride nanorod. Detailed Implementation

[0026] The technical solution of the present invention is further described below, but the scope of protection is not limited to what is described.

[0027] The first embodiment of the present invention relates to a method for preparing tetragonal prism-shaped carbon nitride nanorods. The method involves using a tetragonal prism-shaped silica nanotube as a hard template, impregnating the silica nanotube with a polar solvent, adding a carbon nitride precursor, drying to evaporate the solvent, and then obtaining the tetragonal prism-shaped carbon nitride nanorods through calcination and etching processes.

[0028] The second embodiment of the present invention is largely the same as the first embodiment, except that, in a further preferred embodiment, the polar solvent is N,N-dimethylformamide.

[0029] Furthermore, the mass ratio of the carbon nitride precursor to the tetragonal prism-shaped nano-silica tubes is 1 to 3:1.

[0030] Furthermore, the carbon nitride precursor is any one of thiourea, dicyandiamine, melamine, 3-amino-1,2,4-triazole, and 5-amino-1H-tetrazole.

[0031] Furthermore, the diameter of the tetragonal prism-shaped nano-silica tube is 52nm to 123nm.

[0032] The third embodiment of the present invention is largely the same as the first embodiment, mainly in that it is further refined, such as... Figure 1 As shown, the specific steps are as follows:

[0033] S1. Prepare a gel-like liquid by mixing square prism-shaped nano-silica tubes with a polar solvent;

[0034] S2. Add carbon nitride precursor to the gel-like liquid, heat and stir at 100°C until homogeneous to obtain a white solid.

[0035] S3. Heat the white solid to 500-550℃ at a heating rate of 2-5℃ / min, then calcine it in a muffle furnace for 2-4 hours, and cool it to room temperature to obtain a pale yellow solid.

[0036] S4. Place the pale yellow solid in a 5M-10M HF solution and stir to etch for 24-48 hours. Then filter and wash until neutral. After drying overnight, the yellow solid, namely the tetragonal prism-shaped carbon nitride nanorods, is obtained.

[0037] The fourth embodiment of the present invention is largely the same as the third embodiment, with reference to the second embodiment and a further preferred embodiment provided, namely, the mass ratio of carbon nitride precursor to tetragonal prism-shaped nano-silica tube is 2:1.

[0038] Preferably, the carbon nitride precursor is 3-amino-1,2,4-triazole (3-AT).

[0039] Preferably, the diameter of the quadrangular prism-shaped nano-silica tube is 52 nm.

[0040] Furthermore, the drying overnight condition in step S4 is 60°C.

[0041] Based on the above, steps S1 and S2 in the third embodiment can be simply combined. The specific method of this embodiment is as follows:

[0042] (1) The carbon nitride precursor is uniformly mixed with the tetragonal prism-shaped silica nanotubes.

[0043] A carbon nitride precursor and tetragonal prism-shaped silica nanotubes are uniformly mixed in a certain mass ratio using a solvent. The solvent is DMF, a polar solvent; the carbon nitride precursor is a nitrogen-rich organic small molecule; the tetragonal prism-shaped silica nanotubes have an inner diameter of 52 nm; the uniform mixing of the carbon nitride precursor and the tetragonal prism-shaped silica nanotubes involves first wetting the silica with DMF and then adding it to the precursor, followed by rapid heating and stirring; the mass ratio of the carbon nitride precursor to the tetragonal prism-shaped silica nanotubes is 1 to 3:1.

[0044] (2) The mixture obtained after drying was subjected to thermal polymerization to prepare a pale yellow solid.

[0045] A uniform mixture of carbon nitride precursor and tetragonal prism-shaped silica nanotubes in a certain mass ratio is placed in a covered alumina crucible, which is then placed in a muffle furnace. The temperature is increased to 520-550℃ at a rate of 2-5℃ / min, held for 2-4 hours, and then cooled to room temperature.

[0046] (3) Remove the hard template of the tetragonal prism-shaped silica nanotubes from the light yellow solid obtained after calcination, filter, wash and dry to obtain tetragonal prism-shaped carbon nitride nanorods.

[0047] The pale yellow solid was sonicated in a 5-10 M HF solution and stirred for 24-48 hours to remove the outer shell of the tetragonal prism-shaped silica nanotubes. The filtered yellow solid was washed several times with water and anhydrous ethanol alternately until the solution was neutral. The yellow solid was then removed and dried at 60°C overnight to obtain tetragonal prism-shaped carbon nitride nanorods.

[0048] Experimental Example 1

[0049] Using 0.5 g of tetragonal prism-shaped silica nanotubes as a hard template, a 50 mL single-necked flask was placed in which 7 mL of DMF was added to wet the template. Then, 0.5 g of carbon nitride precursor 3-AT was added. The mixture was heated at 100 °C and stirred until homogeneous. After evaporation and drying, a white solid was obtained and placed in a covered crucible. The crucible was heated to 550 °C in a muffle furnace at a heating rate of 2.5 °C / min and held for 4 h. After cooling to room temperature, the resulting pale yellow solid was placed in a 5 mol·L HF solution and stirred for 24 h to remove the tetragonal prism-shaped silica nanotube hard template agent. The solid was filtered to obtain a yellow solid, which was washed several times alternately with water and anhydrous ethanol until the solid was neutral. The solid was then removed and dried at 60 °C to obtain tetragonal prism-shaped carbon nitride, named TCN-1.

[0050] Experiment Example 2

[0051] It is roughly the same as Experiment 1, except that the mass ratio of the hard template agent to the carbon nitride precursor is: 0.5g of tetragonal prism silica nanotubes and 1g of 3-AT, named TCN-2.

[0052] Experimental Example 3

[0053] The experiment was largely the same as in Example 1, except for the mass ratio of the hard template agent to the carbon nitride precursor: 0.5 g of tetragonal prism silica nanotubes and 1.5 g of 3-AT, named TCN-3.

[0054] The fifth embodiment of the present invention relates to the application of a tetragonal prism-shaped carbon nitride nanorod, characterized in that the tetragonal prism-shaped carbon nitride nanorod prepared by the method described in the first to fourth embodiments above is applied to the photocatalytic degradation of antibiotics in wastewater.

[0055] Experiment Example 4

[0056] The tetragonal prism-shaped carbon nitride nanorods prepared in Experiments 1 to 3 above were used for photocatalytic degradation of the antibiotic tetracycline hydrochloride (TCH) in water, as follows:

[0057] 20 mg of tetragonal carbon nitride nanorods were added to 100 mL of tetracycline hydrochloride (TCH) solution with a concentration of 20 ppm. The solution was sonicated for 3 min and then magnetically stirred for 60 min in the dark to reach adsorption-desorption equilibrium. The solution was then transferred to a 300 W xenon lamp light source equipped with a filter (λ = 420 nm) for photocatalytic degradation. Samples were taken at certain time intervals and analyzed by ultraviolet spectrophotometer.

[0058] like Figure 3 As shown, the tetragonal prism-shaped carbon nitride photocatalysts (TCN-1, TCN-2, and TCN-3) exhibited significant degradation performance, with TCH degradation rates of 83.9%, 86.1%, and 74.7% respectively within 80 min, and BCN (i.e., original carbon nitride, hereinafter the same) degradation rate of 28.8%. This indicates that the tetragonal prism-shaped carbon nitride photocatalysts (TCN-1, TCN-2, and TCN-3) have higher catalytic performance. Compared with TCN-1 and TCN-3, TCN-2 has the best degradation performance because it has a larger specific surface area and a richer pore structure. In contrast, the carbon nitride precursor in TCN-1 did not completely fill the silica hard template, making it difficult to form a rod-shaped structure. In TCN-3, the carbon nitride precursor overfilled the silica hard template, causing the carbon nitride to aggregate into lumps. Too much or too little precursor addition cannot achieve the optimal specific surface area and rich pore structure for the tetragonal prism-shaped carbon nitride. In addition, based on the tetragonal prism-shaped carbon nitride nanorods prepared in Experiment 2 above, adsorption-desorption experiments were conducted, and the results are as follows: Figure 4 As shown, TCN-2 has a higher specific surface area and richer porosity structure than BCN, indicating that this method can effectively increase the specific surface area of ​​the original carbon nitride, increase the number of active sites, and increase the contact surface with the target pollutant, which is beneficial for mass transfer and thus enhances its photocatalytic performance.

[0059] The fifth embodiment of the present invention relates to the application of a tetragonal prism-shaped carbon nitride nanorod. The tetragonal prism-shaped carbon nitride nanorod prepared by the method described in the first to fourth embodiments above is used to determine the stability of antibiotics in wastewater through photocatalytic degradation.

[0060] Experimental Example 5

[0061] The stability determination of the application of prismatic carbon nitride nanorods in the photocatalytic degradation of antibiotics in wastewater was largely the same as in Experiment 4, except that after the photocatalytic degradation experiment of tetracycline hydrochloride (TCH) in water, the catalyst was recovered, washed multiple times with deionized water and anhydrous ethanol, and dried at 60°C for use in the next photocatalytic degradation experiment.

[0062] like Figure 5As shown, the tetragonal prism-shaped carbon nitride photocatalyst TCN-2 exhibits stable degradation performance. After four cycles of experiments, the degradation rate of TCH can still reach 83.6%, indicating that the tetragonal prism-shaped carbon nitride photocatalyst is very stable and highly practical.

[0063] In summary, the above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention.

Claims

1. A method for preparing tetragonal prism-shaped carbon nitride nanorods, characterized in that, Using a quadrangular prism-shaped silica nanotube as a hard template, the quadrangular prism-shaped silica nanotube is impregnated with a polar solvent, a carbon nitride precursor is added, the solvent is evaporated after drying, and quadrangular prism-shaped carbon nitride nanorods are obtained through calcination and etching processes. The specific steps are as follows: S1. Prepare a gel-like liquid by mixing square prism-shaped nano-silica tubes with a polar solvent; S2. Add carbon nitride precursor to the gel-like liquid, heat and stir at 100°C until homogeneous to obtain a white solid. S3. Heat the white solid to 500-550℃ at a heating rate of 2-5℃ / min, then calcine it in a muffle furnace for 2-4 hours, and cool it to room temperature to obtain a pale yellow solid. S4. Place the pale yellow solid in a 5M~10M HF solution and stir to etch for 24h~48h. Then filter and wash until neutral. After drying overnight, the yellow solid, namely the tetragonal prism-shaped carbon nitride nanorods, is obtained.

2. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 1, characterized in that, The polar solvent is N,N-dimethylformamide.

3. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 1, characterized in that, The mass ratio of the carbon nitride precursor to the tetragonal prism-shaped nano-silica tubes is 1~3:

1.

4. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 1, characterized in that, The carbon nitride precursor is any one of thiourea, dicyandiamide, melamine, 3-amino-1,2,4-triazole, and 5-amino-1H-tetrazole.

5. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 1, characterized in that, The diameter of the quadrangular prism-shaped nano-silica tube is 52nm~123nm.

6. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 3, characterized in that, The mass ratio of the carbon nitride precursor to the tetragonal prism-shaped nano-silica tubes is 2:

1.

7. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 4, characterized in that, The carbon nitride precursor is 3-amino-1,2,4-triazole.

8. The method for preparing tetragonal prism-shaped carbon nitride nanorods as described in claim 1, characterized in that, The drying conditions in step S4, which involve drying overnight, are 60°C.

9. An application of a tetragonal prism-shaped carbon nitride nanorod, characterized in that, The tetragonal prism-shaped carbon nitride nanorods prepared by the method described in any one of claims 1 to 7 are applied to the photocatalytic degradation of antibiotics in wastewater.

Citation Information

Patent Citations

  • Hollow tubular carbon nitride photocatalyst and preparation method and application thereof

    CN109603880A

  • Synthesis of nitrogen rich 2d mesoporous carbon nitride with rod shaped morphology and tunable pore diameters

    US20200172397A1